Effect of Post-Heat Treatment on the Mechanical Properties and Corrosion Behavior of Duplex Stainless Steel Fabricated by Wire Arc Additive Manufacturing - Long Zhang; Liang Liu; Feihong Liu; Jian Sun; Dongsheng Wang (Archives of Metallurgy and Materials)
In this study, the effect of heat treatment on the microstructure and mechanical properties of 2209 duplex stainless steel fabricated by wire arc additive was analyzed. It was found that solution treatment at 1100°C for 2 hours and tempering at 300°C for 2 hours can effectively improve the grain inhomogeneity of 2209 duplex stainless steel, eliminate γ2 and harmful brittle phases, and take into account the mechanical properties and corrosion resistance. Compared with the original deposition state, the hardness and yield strength increased by 10% and 31.8% to 245.6 HV and 499.7 MPa, which meet the requirements of engineering propellers. Electron back-scattered diffraction studies showed that the grains became refined and austenite maintained <101>//Z orientation after solution heat treatment. Many small-angle grain boundaries were present in both the original sample and the solid solution, but further tempering transformed the small-angle grain boundaries into large-angle grain boundaries.